On the electric dipole moment of the electron and the P, T-odd electron–nucleus interaction in highly-charged heavy ions. (28th May 2015) - Bondarevskaya, A A; Chubukov, D V; Andreev, O Yu; Mistonova, E A; Labzowsky, L N; Plunien, G; Liesen, D; Bosch, F
Abstract: It is demonstrated that the effect of the electric dipole moment of electron and of the P, T -odd electron–nucleus interaction can be well distinguished in the experiments with H-like (or Li-like) highly charged ions in storage rings. These two effects cannot be separated in the experiments with a certain atom or molecule. Possible experiments for the search of P, T -odd effects with H-like ions in storage rings are discussed and the parameters of these experiments (observation time, field control) are estimated.